1986
DOI: 10.1073/pnas.83.12.4469
|View full text |Cite
|
Sign up to set email alerts
|

A recognition site on synthetic helical oligonucleotides for monoclonal anti-native DNA autoantibody.

Abstract: The binding site in native DNA for a murine monoclonal anti-DNA autoantibody was investigated by measurements of competitive binding of a series of synthetic helical oligonucleotides. The antibody bound to a (dG-dC)3 or (dGdC)4 core in the center of a base-paired octadecanucleotide. Reactions of analogues containing modifications or substitutions at specific sites indicated that the antibody bound to portions of cytosine and guanine in the major groove, a limited region of the backbone, and the 2-amino group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 29 publications
(33 reference statements)
2
46
0
Order By: Relevance
“…The authors showed that the labelling was mainly confined to the condensed chromatin regions of both HeLa and CHO cell nuclei including the peri-and intranucleolar condensed chromatin clumps. Such anti-DNA antibodies used frequently occur in sera from patients suffering from systemic lupus erythematosus (SLE; for reviews see : Stollar, 1975: Stollar, , 1986Tan, 1982;Tan et al, 1988). However, the application of SLE sera is limited because they usually contain a mixture of different antibodies with different specificities (Arana and Seligmann, 1967;Notman et al, 1975;Gilliam et al, 1980) which might include antibodies directed against other nuclear components such as histones and small nuclear RNPs (for review see Tan et al, 1988).…”
Section: Immunolocaliza Tion Of Dnamentioning
confidence: 99%
“…The authors showed that the labelling was mainly confined to the condensed chromatin regions of both HeLa and CHO cell nuclei including the peri-and intranucleolar condensed chromatin clumps. Such anti-DNA antibodies used frequently occur in sera from patients suffering from systemic lupus erythematosus (SLE; for reviews see : Stollar, 1975: Stollar, , 1986Tan, 1982;Tan et al, 1988). However, the application of SLE sera is limited because they usually contain a mixture of different antibodies with different specificities (Arana and Seligmann, 1967;Notman et al, 1975;Gilliam et al, 1980) which might include antibodies directed against other nuclear components such as histones and small nuclear RNPs (for review see Tan et al, 1988).…”
Section: Immunolocaliza Tion Of Dnamentioning
confidence: 99%
“…In retrospect, the ease of production of such Mabs should perhaps have (Campbell, 1984). It is both relevant and interesting to note that in the autoimmune field where similar identification problems have been encountered, (Eilat, 1986;Ghosh & Campbell, 1987) particularly where DNA is the antigen, it is the IgG class of autoantibody that is found only in diseased subjects while the IgM can be found in all individuals (Stollar et al, 1986). Thus, by analogy, it is the IgG class that should be sought in tumour patients.…”
Section: IImentioning
confidence: 99%
“…Recently, it has been reported that cellpenetrating anti-dsDNA autoAbs have multiple arginines in the complementarity determining region 3 of variable heavy domain (CDR3-VH) and one of the Abs, 2C10 IgG and its recombinant VH, penetrate cells (Im et al 2015(Im et al , 2017 and increase the levels of pERK1/2 and Bcl-2 in renal mesangial (MES) cells, the main target in LN (Im et al 2015). 2C10 IgG has been produced from the SLE mouse model MRL-lpr/lpr (Stollar et al 1986;Kubota et al 1996;Im et al 2015). The recombinant 2C10 VH single domain has been produced by engineering the structure of 2C10 IgG (Im et al 2015(Im et al , 2017.…”
Section: Introductionmentioning
confidence: 99%